"We Didn't Know You Were a Negro": Fredric Wertham and the Ironies of Race, Comic Books, and Juvenile Delinquency in the 1950s. Issue 1 (12th April 2017) - Doyle, Dennis
Abstract: In our collective memory of the 1950s, Frederic Wertham often appears as the spearhead of the conservative anti–comic book campaign. Yet in recent historiography, scholars have championed him as an antiracist who made mental health care more available to African Americans at Harlem's Lafargue Mental Hygiene Clinic. Named for Karl Marx's son-in-law, its volunteers provided low-cost care regardless of race from 1946 to 1959. How did someone who might otherwise have been branded a Communist attract white conservative allies at the repressive outset of the Cold War? This paper contends that this leftist was able to keep his subversive clinic open for thirteen years because that white public was unaware its patients and staff were black. The Lafargue Clinic relied on mass media to generate donations. In the 1950s, the clinic's public image was linked to the anticomics movement. Because Wertham represented the work he did there with children and comics in a race-neutral fashion, white parents thought the clinic was white, flooding it with donations and requests for speakers. Ironically, this radical clinic was forced to close once the anticomics crusade ended, eroding its conservative base. The history of the Lafargue Clinic's public image highlights the ironies of a postwar United States united by mass media. A carefully crafted public image enabled some subversive institutions to avoid the blacklist and pursue their missions. By generating allies ignorant of their actual activities and ideology, places such as the Lafargue Clinic managed to survive the 1950s—hidden in plain sight.